Sequenced problems for functional equations - Ádám, Zsolt; Lajkó, Károly; Maksa, Gyula; Mészáros, Fruzsina (Teaching Mathematics and Computer Science, 2006)
There are many possible methods to solve equations of the form H(f(x + y), f(x − y), f(x), f(y), x, y) = 0 (x, y 2 R), where H is a known function and f is the unknown function to be determined. Here we will create a sequence of problems for equations of type (1) (see on the next page). These sequenced problems are appropriate for the fostering of talented students on different level of mathematical education.